A comprehensive study on 2D, 3D and solid tumor environment to explore a multifunctional biogenic nanoconjugate - B. S. Unnikrishnan (Nature Portfolio, 2021)
Abstract Emergence of nanotechnology created a drastic change in the field of cancer therapy due to their unique features in drug delivery and imaging. Polysaccharide based nanoparticles have received extensive attention in recent years as promising nanoparticle mediated drug delivery systems. Polysaccharides are endorsed with versatile merits including high drug encapsulation efficiency, efficient drug protection against chemical or enzymatic degradation, unique ability to create a controlled release and cellular internalization. In the current study, we have fabricated doxorubicin-loaded carboxymethylated PST001 coated iron oxide nanoparticles (DOX@CM-PST-IONPs) for better management of cancer. CM-PST coated iron oxide nanoparticles co-encapsulated with chemotherapeutic drug doxorubicin, can be utilized for targeted drug delivery. Biocompatible and non-toxic nanoconjugates was found to be effective in both 2-D and 3-D cell culture system with efficient cancer cell internalization. The bench-marked potential of CM-PIONPs to produce reactive oxygen species makes it a noticeable drug delivery system to compact neoplasia. These nanoconjugates can lay concrete on a better way for the elimination of cancer spheroids and tumor burden.